To the question of formation of earthquakes of corporate structures of agricultural production - Kustovskaya, O.; Novak, M. (Land Management, Cadastre and Land Monitoring, 2017)
The article analyzes the development of corporate structures in agricultural production, proves the influence of corporate formations on the efficiency of agrarian production. On the basis of the analysis of official information of agro holdings, an assessment was made of the efficiency of their activities and a conclusion was made about the optimal size of their structural subdivisions. The advantages and disadvantages of integrated structures are highlighted, peculiarities of formation of their land relations are determined. Issues of expansion of land masses of agro holdings related to the conclusion of land lease agreements are considered.The association of separate agro-industrial enterprises of various industrial-economic orientation form an independent legal entity - a legal entity. The economic feasibility of the creation and functioning of corporate associations is objective based on obtaining the greatest effect, the essence of which is that the result of the joint corporate activities of economic structures will always be higher compared to the results of the individual work of each of them.Corporate forms of management in agriculture were founded in Ukraine on the basis of the general theoretical model of an open, competitive, multi-faceted agricultural market economy type, aimed at an integrated world economic system. The methodology of construction involves taking into account the world economic trends and the national specificity of the country's agricultural development; it is aimed at finding rational forms of organization of agricultural production, mechanisms for overcoming crisis phenomena, stabilizing the economy and creating conditions for further qualitative and quantitative growth of the agrarian sector of the economy. For many years, leading American co-operators have been distributing concepts and concepts that are perceived and used throughout the world. This work is coordinated by the Organization for International Cooperative Development in Agriculture, and thanks to its efforts, many countries in the world have implemented projects for the development and strengthening of cooperative organizations owned by agricultural producers. The experience of cooperative and corporatization in the US agriculture can be useful for restructuring the agriculture of countries undergoing a stage of market transformation, and Ukraine has the necessary conditions for developing, along with production agricultural cooperatives, corporate and partner forms of management.The essence of corporate structures in agriculture consists in the grouping of owners of land and property, funds of agricultural enterprises in a certain form of organization. The highest form of corporate education is considered to be those in which not individuals are integrated, but enterprises of different profile who work for the final consumer product.The consolidation of the land masses of agricultural holdings is largely due to the advantages of integrated structures: firstly, significant savings on the scale of acquisition of means of production: second, not new conditions of collateral - agricultural products are a pledge for non-agricultural activities of holdings.In order to improve the procedure for forming the land masses of integrated structures, it is necessary to: improve the system of state land resources management, continue to formulate the necessary legislative and normative base on issues of agrarian land use and functioning of the agricultural land market; to form an effective mechanism for the functioning of a fully-fledged, state-regulated market of agricultural land: to improve the economic mechanism of regulation of land relations.Keywords: corporate structures, agricultural production, efficiency, production activity, market economy.